Place-name Mutation Variation in Wales and Patagonia. (1st January 2020) - Sleeper, Morgan
This study uses corpus data of modern conversational speech to examine variation in the mutation of place-names in Welsh as spoken in both Wales and Patagonia. Specifically, it considers how speakers from both areas mutate (or do not mutate) place-names following the nasal mutation trigger yn 'in', through a two-step statistical approach of conditional inference trees and random forests. Results show no significant difference in how speakers from Wales and Patagonia mutate place-names in this environment, but that the radical initial consonant, speaker age, and place-name type – including the geographical, linguistic, and cultural 'Welshness' of the place-name – all significantly affect mutation behaviour. Furthermore, while nasal mutation is present in the data, the results also illustrate the growing use of soft mutation as an alternate mutation strategy following yn.